Pengaruh Kompetensi Dan Disiplin Terhadap Kepuasan Serta Implikasinya Pada Prestasi Kerja Karyawan - Hendra Hadiwijaya; Agustina Hanafie (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
Influence of competence and discipline to satisfaction and the implications on performance.Aims to identify and analyze the level of influence directly and indirectly and which variable has more influence on employee performance on Insurance AJB Bumi Putera 1912.This research analyzes using Structural Equation Modelling.The results showed variable competency has a greater direct influence on satisfaction of 0.32 compared to only 0.14 Discipline.Competence has a direct influence most to the achievement of 0.28, compared Discipline and Satisfaction 0.11 and 0.05. Variable discipline greater indirect effect on the achievement of 0.37, of the competence of 0.19